Systematic overview of neuroanatomical differences in ADHD: Definitive evidence - Vieira De Melo, Bruno (2019)
Objectives: This article seeks to identify neuroanatomical differences in ADHD through an overview of systematic reviews that report encephalic differences compared to a control group in volume, area, activation likelihood or chemical composition. Methods: We conducted a systematic search using Cochrane guidelines and PRISMA criteria in PubMed, Scopus, Web of Science, Cochrane Database of Systematic Reviews and Database of Abstracts of Reviews of Effects. Results: Results revealed broad encephalic involvement that includes a functional frontal and cingulate hypoactivation and structural differences in corpus callosum, cerebellum and basal nuclei. Conclusions: ADHD symptoms might be due to a multi-network unbalanced functioning hypothesis.